Polyurethane - Zafar, Fahmina; Sharmin, Eram (IntechOpen, 2012)
The enchanting and worthy world of PU beckoned to bring forth the book titled "Polyurethane". The book is divided into three sections: structures, properties and characterization of PU, applications of PU and a separate section on Biobased PU, covering the research and development in these areas. Each contributed chapter handles new and interesting topics introducing the reader to the wider known and unknown applications of PU such as PU for grouting technologies, fuel binder, extraction of metals, treatment of industry wastewater, alkanolamide PU coatings and foams, and others. The book aims to cater a larger audience comprising of readers from polymer chemistry, materials chemistry, and industrial chemistry.